FORMULATION AND TEST OF ANTIBACTERIAL ACTIVITY OF LIQUID SOAP EDAMAME SEED EXTRACT (Glychine max. Merr) AGAINST BACTERIAL GROWTH Staphylococcus aureus - Wanda Tri Agustin; Dhina Ayu Susanthi; Aliyah Purwanti (LPPM Universitas dr. Soebandi, 2025)
Skin infection can be caused by Staphyloccocus aureus bacteria that attack normal skin. Infections can be prevented by giving antibiotics, but bacterial resistance is reported to be increasing, therefore we must create new product development innovations. One of the product development innovations that will be made is liquid soap of edamame seed extract by utilizing natural ingredients. to formulate and test the antibacterial activity of liquid soap of edamame seed extract against the growth of Staphyloccocus aureus bacteria. This study aims to formulate and test the antibacterial activity of liquid soap of edamame seed extract against the growth of Staphyloccocus aureus bacteria. Ethanol extract of 96% edamame seeds (Glycine max. Merr) was obtained using the UAE method. Furthermore, a liquid soap preparation of edamame seed extract was formulated with concentrations of F1 (5%), F2 (10%), F3 (15%). Then after that, physical properties such as pH test, organoleptics, foam height, dispersion, homogeneity and antibacterial activity were tested using the well diffusion method. The data was analyzed using the One Way anova test method followed by the Post hoc test, namely LSD. Liquid soap of edamame seed extract is tested for physical quality where the results obtained have met all the parameters of the physical quality test. The average antibacterial test results for the concentration of F1 (5%) in the inhibition zone were 14.66 mm, F2 (10%) in the inhibition zone was 15.29 mm, and F3 (15%) in the inhibition zone was 16.57 mm and the Control (+) inhibition zone was 18.83 mm. The results of the One Way Anova analysis on the anti bacterial test with a significant value of 0.199 showed that there was no difference in each concentration on the effect of the inhibitory power of Staphylococcus aureus bacteria. It can be concluded that the liquid soap formulation that has been tested for physical quality has met the predetermined requirements. For the antibacterial test carried out on the three formulations made, the best results were produced by F3 (15%) with an inhibitory zone diameter of 16.57 mm.